Pemahaman Mahasiswa Stiepar Yapari tentang Materi Pelatihan Pentingnya Kebersihan dalam Proses Memasak - Sean Miguel Boubon; Muhammad Abhell Rayhan Alfiqri; Fairuz Machiavalli (Tamasya : Jurnal Pariwisata Indonesia, 2025)
This study aims to measure the understanding of STIEPAR Yapari students regarding the training material on the importance of cleanliness in the cooking process. This training is given as part of strengthening student competencies in the field of tourism and hospitality, especially in the aspect of food sanitation. The method used was a quantitative survey with the distribution of questionnaires to the training participants. The results of the study showed that most students have a good level of understanding of hygiene materials, including the importance of washing hands, maintaining cooking utensils, and managing foodstuffs hygienically. These findings confirm that the training is effective in raising awareness of the importance of cleanliness as part of operational standards in the culinary and hospitality industry. This understanding also supports the creation of safe and quality food services. It is hoped that similar training can be carried out on an ongoing basis to strengthen student professionalism.